Development UMKM of Cantir Cruiser with Cassava-Based Ingredients in Dayeuhluhur Village - Yuda Agustira, Ade; Selviani, Tasya Bilqis; Fadhilah, Rikza; Syakinatunnisa, Nindhita; Meilawati, Mila; Rasyid, Fahmi; Azis, Dika Dwi Muhammad; Murni, Chintia; Puspitawati, Alin; Fadzilah, Aldy Rinaldy; Anggraeni, Yunissa (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Ciparahu Hamlet, Dayeuhluhur Village, Dayeuhluhur District, Cilacap Regency, Central Java Province is one of the cassava producing areas which is quite a lot so that the selling price of cassava in the village of Daeyuhluhur is quite low. Development of Micro, Small, and Medium Enterprises in Indonesia known as Usaha Mikro Kecil Menengah (UMKM). With developments in this globalization era, it is very dependent on the economic sector as a measure of success carried out by the government. UMKM are a form of productive economic enterprise carried out by individuals or individual business entities that meet the criteria for micro, small and medium enterprises. One of the efforts to increase the selling power of cassava, Dayeuhluhur villagers process cassava with various kinds of processed food, one of which is cantir crackers. The development of micro, small and medium enterprises from cantir crackers made from cassava is enough to attract the local community.